The Outlook of Cyber Security in African Businesses: Issues and Way-Out - Adeniran , Adedayo Ayomide; Adeniran, Adetayo Olaniyi; Familusi, Olayemi Babawole; Adedayo, Oluwafemi (Management Analytics and Social Insights, 2024)
This study explores the outlook of cyber security in African businesses. Issues and ways out in a changing environment were highlighted. Cybersecurity measures need to be strengthened because cybercrime is estimated to cost the African continent about $10 billion annually. With just 20,000 certified cyber security specialists in Africa compared to over 1.3 million in the US, the study emphasizes African firms' low awareness and understanding. Based on empirical research and worldwide cyber security indexes, the paper analyzes the main obstacles to successful cyber security measures, such as resource limitations, knowledge gaps, and insufficient legislative frameworks. It also delved into real-world implementation problems, including disjointed infrastructure and linguistic hurdles. The report suggests cyber security awareness, utilizing technology, and encouraging cooperation through public-private partnerships to minimize these issues. The study further highlights the application of Artificial Intelligence (AI), which is revolutionizing cyber security defenses and promoting the adoption of cyber security in Africa. African businesses can negotiate the complicated cyber security landscape, resulting in a more reliable and secure digital environment and enormous potential for economic growth.